Correlation between radiographic signs of third molar proximity with inferior alveolar nerve and postoperative occurrence of neurosensory disorders: A prospective, double-blind study - Costa,Fábio Wildson Gurgel (2013)
PURPOSE: To evaluate the interference of radiographic factors in the appearance of sensory deficit related to inferior alveolar nerve (IAN) after third molars (3Ms) removal. METHODS: A prospective, double-blind, observational, unicentric study was performed with 126 patients submitted to a surgical procedure of lower 3Ms removal in the period from March to October/2011. Collected data included gender, age, eruption stage of 3Ms, position/angle of 3Ms (Pell-Gregory and Winter classifications, respectively), presence/absence of radiographic signs of 3Ms proximity with the inferior alveolar canal and surgical technique. Occurrence evaluation of the IAN injury was performed on the seventh postoperative day through pin-prick, two-point discrimination and brush directional stroke tests. RESULTS: Predominant radiographic signs were: narrowing of the inferior alveolar canal (68.25%), darkening of root (46.82%) and diversion of the canal (31%). None of the patients presented sensory loss. Sixty-one (48.41%) of the cases had at least one or two radiographic signs of proximity with NAI. Forty-seven (37.3%) had 3 or more signs, and 18 (14.29%) did not have any radiographic signs of proximity to mandibular canal. CONCLUSION: There was not a positive correlation between presence of radiographic signs of 3Ms with IAN proximity and postoperative neurosensory disorders occurrence.